Analisis Akurasi Nilai Peramalan Data Transaksi Perusahaan Jasa Menggunakan Kombinasi Metode K-Means Clustering dan Metode Deret Berkala - Santi Ika Murpratiwi; Dewa Ayu Indah Cahya Dewi; Arik Aranta (Journal of Computer Science and Informatics Engineering (J-Cosine), 2021)
Profit decline is a frightening problem for service companies. The solution to prevent this is by analyzing data transactions using data mining and forecasting. K-Means used to cluster the level of car damage based on the number of panels repaired and the duration of repaired. The results of K-Means used as material for analysis the best time-series method for transaction data. The methods analyzed include the moving average, single exponential smoothing, double exponential smoothing, and winter's method. Single exponential smoothing is the most suitable forecasting method with transaction data. Based on the MAPE value obtained for minor damage of 12.58%, forecasting for moderate damage of 16.83%, forecasting for major damage of 17.31%, and forecasting for overall data of 8.0975%. It concluded that single exponential smoothing can apply with K-Means clustering and the company can use it to make strategies to prepare the number of workers and production materials required.